PENGEMBANGAN SUMBER DAYA KEUANGAN BERDASARKAN PERATURAN GUBERNUR NOMOR 97 TAHUN 2022 DI SMA NEGERI 1 PURWAKARTA - Deti Rostini; Wiwik Dyah Aryani; Apriadi Manan; Asep Yuliana; Nana Ismelani (BUANA ILMU, 2023)
Peraturan Gubernur Nomor 97 Tahun 2022 provides an opportunity for the development of financialresources that do not only come from the government, this regulation regulates education funding thatcomes from the community. By using a qualitative approach and a descriptive study design throughobservation, interview and documentation data collection techniques in this study it shows that the initialsteps taken by SMA Negeri 1 Purwakarta in responding to Peraturan Gubernur Nomor 97 Tahun 2022are conducting socialization and formulating the Rencana Kegiatan dan Anggaran Sekolah (RKAS) bysorting out the budget originating from BOS (School Operational Assistance) and BOPD (RegionalEducation Operational Assistance) funds as well as shortages of school operational costs which will bemet through fundraising by the Komite Sekolah. After the funds have been collected, these funds arehanded over to the school principal as the manager of the institution to finance school operations inaccordance with the plan contained in the RKAS. The school principal as the manager of the budget isobliged to report the budget that has been used to the Komite Sekolah and then the Komite Sekolah reportsit to the parents of students through the Rapat Komite Sekolah.